Perlindungan Konsumen Dalam Penyelesaian Sengketa Sektor Keuangan (Studi Komparatif LAPS-SJK Dan BPSK) - Pramesti, Mutiara; Njatrijani, Rinitami; Widanarti, Herni (Faculty of Law, Diponegoro University, 2025)
This article discusses the legal protection provided by 2 (two) consumer dispute resolution institutions, namely the Financial Services Sector Alternative Dispute Resolution Institution (LAPS-SJK) and the Consumer Dispute Resolution Agency (BPSK). This article focuses on a comparison of the legal force of decisions issued by the two institutions. By combining normative legal views and the opinions of practitioners consisting of the Financial Services Authority (in this case represented by OJK Central Java Province) and the Consumer Dispute Resolution Body (in this case represented by BPSK Semarang City), this article can underline the optimization of consumer protection in disputes with business actors in the financial services sector. This article can show the complementary side of BPSK with the presence of LAPS-SJK as an institution that handles disputes in the financial sector. This article aims to present a comparison between LAPS-SJK and BPSK as alternative resolution institutions resulting from a combination of factual events and practitioners' opinions with the analytical knife being the applicable laws and regulations.